Airside friction and heat transfer characteristics for staggered tube bundle in crossflow configuration with diameters from 0.5 mm to 2.0 mm. (July 2016) - Bacellar, Daniel; Aute, Vikrant; Huang, Zhiwei; Radermacher, Reinhard
Highlights: Airside correlations for heat transfer and friction characteristics of bare tube heat exchangers using diameters ranging from 0.5 mm to 2.0 mm. The correlations are developed for an unprecedented design space as follows: 2–40 tube rows, 1.2–4.0 times tube diameter for both transverse and longitudinal pitches, air velocities from 0.5 m/s to 7.0 m/s. The proposed correlations predict more than 80% of source data within 10% error and more than 90% of the source data within 20% error. Experimental validation was carried out for one heat exchanger with 15 data points. Abstract: This article presents equations for air-side friction and heat transfer characteristics for bare tube air-to-refrigerant heat exchangers with tube diameters ranging from 0.5 mm to 2 mm. There are no air-side correlations for such small diameter tubes in the literature. Furthermore, conventional empirical correlation development relies on testing of samples, which is inherently time consuming, expensive and has a limited range of applicability. The correlations presented in this article are developed based on comprehensive CFD simulations for a large design space and include experimental validation. The proposed correlations predict more than 80% of source data within 10% error and more than 90% of the source data within 20% error. The proposed correlations are valid for 2–40 rows of tubes.